Legal Analysis of Law Number 8 Year 2011 Article 10 Paragraph 1 Regarding Final Constitutional Court Decisions - Abi Sugara (JUSTICES: Journal of Law, 2023)
The Constitutional Court is one of the institutions of judicial power that has the authority to adjudicate cases and also resolve cases from the first level to the last level. the decision has been issued by the constitutional court, the decision has no further legal continuation, that's why the law gives the constitutional court four powers to become one of the institutions that can enforce law and justice in Indonesia and the four powers are: 1) examine UUD 1945 2) decide on an authority dispute between state institutions whose authority has been granted by the state based on the 1945 Constitution 3) decide on the dissolution of political parties 4) decide on disputes over election results, a decision if it has been issued by the constitutional court, the decision is final and also binding so that in this case it causes a positive impact and also a negative impact in the decision, this study has the aim of knowing the meaning and significance of the final decision and what the impact of the decision of the constitutional court which is final and binding, this type of research is juridical normative legal research, namely research with data collection techniques from books, journals or articles and also theses and is equipped with primers from the results of the 1945 Constitution analysis.